1987
DOI: 10.1126/science.235.4785.193
|View full text |Cite
|
Sign up to set email alerts
|

Outward-Dipping Ring-Fault Structure at Rabaul Caldera as Shown by Earthquake Locations

Abstract: The locations of a large number of earthquakes recorded at Rabaul caldera in Papua New Guinea from late 1983 to mid-1985 have produced a picture of this active caldera's structural boundary. The earthquake epicenters form an elliptical annulus about 10 kilometers long by 4 kilometers wide, centered in the southern part of the Rabaul volcanic complex. A set of events with well-constrained depth determinations shows a ring-fault structure that extends from the surface to a depth of about 4 kilometers and slopes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(68 citation statements)
references
References 7 publications
2
66
0
Order By: Relevance
“…This caldera widened considerably during continuing subsidence by the formation of peripheral normal faults and landslides. Images provided by Japanese National Institute of Information and Communications Technology (NICT), 2007 inward-dipping ring faults are evident at Rabaul, Papua New Guinea (Mori and McKee 1987), whereas caldera collapse at Fernandina, Galapagos in 1968 apparently occurred along inward-dipping ring faults (Simkin and Howard 1970), a configuration also known from eroded calderas in the Western USA (Lipman 1984). While inward-dipping ring faults may cause a "space problem" during subsidence to prohibit major conduit opening (Branney 1995), outward-dipping faults are rarely observed at the surface due to landslide processes (Lipman 1984).…”
Section: Structural Architecture and Kinematics Of Ring-faultsmentioning
confidence: 99%
“…This caldera widened considerably during continuing subsidence by the formation of peripheral normal faults and landslides. Images provided by Japanese National Institute of Information and Communications Technology (NICT), 2007 inward-dipping ring faults are evident at Rabaul, Papua New Guinea (Mori and McKee 1987), whereas caldera collapse at Fernandina, Galapagos in 1968 apparently occurred along inward-dipping ring faults (Simkin and Howard 1970), a configuration also known from eroded calderas in the Western USA (Lipman 1984). While inward-dipping ring faults may cause a "space problem" during subsidence to prohibit major conduit opening (Branney 1995), outward-dipping faults are rarely observed at the surface due to landslide processes (Lipman 1984).…”
Section: Structural Architecture and Kinematics Of Ring-faultsmentioning
confidence: 99%
“…For both types the axes of the cones are approximately vertical. In a few cases, microearthquake locations at active volcanoes show evidence of current activity on such structures, for example on nearvertical faults at Rabaul caldera on New Britain [Mori and McKee, 1987]. If dip-slip shear faulting occurs on a conical fault, and the rupture in an earthquake spans a significant azimuth range (Figure 8), the resulting mechanism, considered as a point source, can have a non-DC component [Ekstr6m, 1994].…”
Section: Volcanic Eruptions the Eruption Of Mate-mentioning
confidence: 99%
“…The pattern of surface-projected seismicity was first represented as a "D"-shaped zone (Cooke 1977), and subsequently as two inward-facing arcuate zones, on the eastern and western sides of the caldera (Almond and McKee 1982). Later analysis suggested that the seismicity was related to a ring fault system (Mori and McKee 1987;Itikarai 2008) elongated north-south. The distribution of caldera seismicity for this period (1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)) is shown in Fig.…”
Section: -1983mentioning
confidence: 99%